Parental Ethics in Child Education within the Family Context: A Literature Review from the Perspective of Islamic Education - Martatik; Ahmad Hisyam As Sibli; MiftahurRisqi Sirat; Benny Prasetiya (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to examine the role of parents’ morality in children’s education within the family environment from the perspective of Islamic education. The research employed a literature review method with a descriptive qualitative approach by collecting data from scientific journals, books, and previous studies related to family education, character education, and morality in Islam. Data sources were obtained from several academic databases such as Google Scholar, Scopus, Garuda, and accredited Islamic education journals published between 2020 and 2026. The data were analyzed using content analysis to understand the concepts, methods, and relevance of moral education within the family in the modern era. The findings reveal that the family is the first and primary educational environment in shaping children’s character. Parents’ morality greatly influences children’s moral, social, and spiritual development because children tend to imitate the behavior of their parents as the main role models in their lives. Moral education within the family is implemented through exemplary behavior, habituation, advice, attention, and supervision based on Islamic values. In addition, this study found that the educational thoughts of Abdullah Nashih Ulwan and Maria Montessori are relevant in character building through educational approaches emphasizing role modeling, positive learning environments, and holistic character development. In the digital era, the role of parents as primary role models becomes increasingly important in guiding children to face the negative impacts of technology and globalization without losing moral and spiritual values